Faculty Senate, Minutes, April 19, 2012 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2012)
Valdosta State University. Faculty Senate, Minutes, April 19, 2012. Chairperson, Louis Levy; Vice Chairperson, Philip Gunter; Executive Secretary, Tracy Woodard-Meyers; Parliamentarian, Ed Walker;
1 electronic document. Faculty Senate, Minutes, April 19, 2012. 30 pages.
Keywords: Minutes (Records); Committees; Electronic records; Valdosta State University. Faculty Senate